2015
DOI: 10.1515/pjvs-2015-0076
|View full text |Cite
|
Sign up to set email alerts
|

Cytological evaluation of tracheal aspirate and broncho-alveolar lavage fluid in comparison to endoscopic assessment of lower airways in horses with recurrent airways obstruction or inflammatory airway disease

Abstract: The aim of the present study was to compare the grade of discharge accumulation in the tracheal lumen, area of tracheal bifurcation, main bronchi and the tracheal septum thickness with the cytology of the tracheal aspirate (TA) and broncho-alveolar lavage fluid (BALF) in horses with recurrent airways obstruction and inflammatory airway disease from those horses. This study was conducted on 96 horses with RAO, 139 horses with IAD and 10 control horses. In all the horses, both clinical and endoscopic examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
3
8
1
Order By: Relevance
“…Enumeration of cells, including the area chosen on the slide (De Brauwer et al 2000;Fernandez et al 2013) and the number of cells counted (De Brauwer et al 2002;Richard et al 2010;Fernandez et al 2013) can also explain the observed variation. Furthermore, the identification and counting of BAL cells has not been considered previously as part of the inaccuracies of the equine BAL procedure, and the importance of experienced counters has seldom been questioned in research papers including BAL cytology results (Robinson et al 2006;Hoffman 2008;Wysocka and Klucinski 2015;Orard et al 2016). Laboratory variation should be avoided whenever possible and thus experience amongst observers is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enumeration of cells, including the area chosen on the slide (De Brauwer et al 2000;Fernandez et al 2013) and the number of cells counted (De Brauwer et al 2002;Richard et al 2010;Fernandez et al 2013) can also explain the observed variation. Furthermore, the identification and counting of BAL cells has not been considered previously as part of the inaccuracies of the equine BAL procedure, and the importance of experienced counters has seldom been questioned in research papers including BAL cytology results (Robinson et al 2006;Hoffman 2008;Wysocka and Klucinski 2015;Orard et al 2016). Laboratory variation should be avoided whenever possible and thus experience amongst observers is important.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the identification and counting of BAL cells has not been considered previously as part of the inaccuracies of the equine BAL procedure, and the importance of experienced counters has seldom been questioned in research papers including BAL cytology results (Robinson et al . ; Hoffman ; Wysocka and Klucinski ; Orard et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In some horses with chronic or recurrent infectious disease, measurement of immunoglobulin concentrations may help identify an underlying immunodeficiency. [240][241][242][243][244][245][246] The primary means of sampling the lower respiratory tract include bronchoalveolar lavage and tracheal wash. Tracheal wash is often used for the diagnosis of infectious pneumonia. Although findings are often nonspecific, serum amyloid A and fibrinogen are two biomarkers commonly used to evaluate inflammatory disease.…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%
“…In another study, clinically normal foals aged 6 months had significantly higher eosinophil counts (2.2%) than foals aged 1 week or 1 month (0%), and yearlings (1.5%) had a higher percentage of eosinophils than adults (0.3%) (Hostetter et al ). Eosinophils counts are low in respiratory secretions of adults regardless of demographics, sampling techniques including TTA or BAL, or quantification method, with differential counts consistently under 3% (Mair et al ; Derksen et al ; Sweeney et al ; Dixon et al ; Moore et al ; Hare and Viel ; Christley et al ; Couetil et al ; Depecker et al ; Wysocka and Klucinski ), or subjectively few (Whitwell and Greet ; Pacheco et al ). Up to 44% of horses have no eosinophils (Beech ; Whitwell and Greet ; Sweeney et al ).…”
mentioning
confidence: 99%
“…Across studies, 5 to 27% of horses with coughing, poor performance or IAD have eosinophils in their respiratory secretions; therefore, upwards of three‐quarters of affected animals may not have eosinophils ( Fig ) (Beech ; Whitwell and Greet ; Hughes et al ; Hughes et al ). When present, eosinophil counts are often still below 3% (Couetil et al ; Richard et al ; Hughes et al ; Wysocka and Klucinski ) or subjectively scored as few (Winder et al ), but mean eosinophil counts of 3.8 to 11.8% and individual counts up to 54% are reported in horses with poor performance or exercise intolerance (Moore et al ; Hare and Viel ; Hughes et al ). When horses are categorised as IAD based upon BALF neutrophils or mast cells, eosinophils are found more frequently and at higher percentages in controls (Hughes et al ).…”
mentioning
confidence: 99%